Determination of phenological stage and nitrogen application dose in linseed crops - Roza, João Pedro Dalla (2024)
This study aimed to evaluate the effects of nitrogen doses on different phenological stages of linseed development during three agricultural years of cultivation. A randomized blocks experimental design was employed, organized in a three-factor design (3x5x3), consisting of three nitrogen applications (beginning of development of basal branching, pre-flowering, and grain filling), five doses of nitrogen (0; 30; 60; 90, and 120kg ha-1), and three agricultural harvests (2020, 2021, and 2022). Each treatment had three replications, totaling 135 experimental units. At full physiological maturity, the crop cycle was evaluated, then 10 plants were randomly collected per experimental unit, the following characters were evaluated and measured: plant height, stem diameter, number of basal branches, height of insertion of the first capsule, grain weight per plant, number of grains per plant, number of branches per plant, and number of capsules. The analysis of variance was conducted at a 5% probability of error using the F test. The variables that showed a significant interaction were broken down to simple effects via polynomial regression with adjustment of the highest degree of the polynomial. The maximum technical nitrogen efficiency for linseed cultivation is 69.8 kg per hectare. Nitrogen fertilization at the basal branching stage enhances grain weight, number of grains per plant, and grain yield. The application of nitrogen when filling grains enhances grain productivity (> 1.6 tons of grains per hectare) regardless of the agricultural year.